Examining the Perinatal Results in Patients Suffering from Acute Fatty Liver of Pregnancy - Christy Vijay; Annamma Thomas; Angeline Yvette Mascarenhas; Naveen Ramesh (Achievements and Challenges of Medicine and Medical Science Vol. 13, 2025)
Introduction: Acute fatty liver of pregnancy (AFLP) is a rare obstetric emergency requiring immediate attention and intensive care to avoid adverse outcomes for the mother and fetus. High morbidity and mortality are seen among women with AFLP. As this condition poses many complications and is varied in its clinical presentation, the perinatal outcomes in women diagnosed with AFLP were studied. Materials and Methods: This was a retrospective study that involved all patients over the past 6 years who presented with AFLP. Clinical signs and other altered biochemical parameters were included. Results: In the study, 19 women were diagnosed to have AFLP. The mean age of the study population was 25.74 \(±\) 3.7 years. 14 (73.68%) women were below the age of 30 years. A gestational age of more than 37 weeks was seen in 13 (68.42%) women. Ten primigravidae (52.63%) and nine multiparous (47.3%) women were found to present with AFLP. The mean blood loss at the time of delivery for a lower-section cesarian section and vaginal delivery was 787.5\(±\)494.07 mL and 280\(±\)44.72mL, respectively. The preferred treatment at the time of admission was transfusion of fresh frozen plasma (FFP) (Mean: 7.00\(±\)9 pints), followed by transfusion of platelet (Mean: 2.37\(±\)3.515 pints), transfusion of packed red blood cells (Mean: 2.21\(±\)3.691 pints) and cryoprecipitate (Mean: 0.0\(±\)2 pints). Nine ( 47.37% ) women were delivered through emergency lower segment cesarean section (LSCS) and all 4 (21.05%) pregnant women who succumbed to AFLP underwent an LSCS. Among the newborns, 13 (65%) of them were low birth weight and 2 (10.53%) had fetal distress. Conclusion: This study showed a higher maternal mortality rate of 21% in comparison to other studies. Health professionals should be sensitized about this condition and the use of the existing scoring system available to help in detecting AFLP at an early stage to reduce maternal mortality and adverse fetal outcomes. Blood loss at the time of delivery makes it imminent to arrange for appropriate treatment and supportive care in the management of the patient, which includes fresh frozen plasma transfusion which was found beneficial in the patients.